Core-shell structure flame retardant with thermo-oxidative aging resistance and application of core-shell structure flame retardant in preparation of flame-retardant material

By forming a core-shell structure containing low-valence phosphorus or hindered phenol on the surface of the flame retardant, the problem of migration and precipitation of flame retardants and antioxidants in polymer materials is solved, thereby improving the flame retardant and antioxidant properties of the material and extending its service life.

CN119264547AActive Publication Date: 2025-01-07UNIV OF SCI & TECH OF CHINA +1

Patent Information

Application Number
CN202411692740.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In existing flame-retardant polymer materials, flame retardants and antioxidants are prone to migration and precipitation during long-term use, which leads to a deterioration in the anti-aging and flame-retardant properties of the polymer materials.

Method used

Flame retardants with a core-shell structure are used. The shell is formed by free radical polymerization of low-valent phosphorus or hindered phenolic compounds, while the core is a flame retardant. The shell not only improves the surface and interfacial properties and water resistance of the flame retardant, but also has antioxidant function, thereby improving the aging resistance of the material.

Benefits of technology

This technology enables long-term resistance to migration and exudation of flame retardants in polymer composites, improving the flame retardant and antioxidant properties of the materials and extending their service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264547A_ABST
    Figure CN119264547A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell structure flame retardant with a thermo-oxidative aging resistance function and application of the core-shell structure flame retardant in preparation of a flame-retardant material, and belongs to the technical field of flame retardance. The core-shell structure flame retardant with the thermo-oxidative aging resistant function is composed of the core and the shell structure, the core is the flame retardant, the shell structure is a polymer containing hindered phenol and low-valence phosphorus, on one hand, hydrophobicity of the flame retardant can be improved, on the other hand, compatibility and dispersity of the flame retardant in a polymeric material can be improved, and the flame retardant performance is improved. Further, the flame retardant property and the mechanical property of the polymer material are improved. Besides, hindered phenol and low-valence phosphorus in the shell polymer not only can capture RO.and ROO.free radicals and inhibit the thermo-oxidative aging process of the polymer, but also can play a role in capturing the free radicals in the combustion process, so that the flame retardant property of the polymer material is further improved. The flame retardant disclosed by the invention has excellent flame retardance and thermal aging resistance, and can be applied to the fields of buildings, traffic, chemical engineering, machinery, communication, energy sources and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardancy, and in particular relates to a core-shell structure flame retardant with anti-thermal oxygen aging function and application thereof in the preparation of flame retardant materials. Background Art

[0002] Polymer resins have excellent toughness, strength, wear resistance, impact resistance, low temperature resistance and other advantages, and are widely used in construction, transportation, chemical industry, machinery, communication and other related fields. However, most polymer materials are flammable materials, which can easily be ignited during use, causing fires. At the same time, polymer materials are also easily degraded by thermal oxidation during long-term service, causing spots, silver streaks, cracks, frost, powdering and gloss color changes on the surface of the product, resulting in comprehensive degradation of the mechanical, electrical and service properties of the polymer material. For this reason, flame retardants and antioxidants need to be added to improve the flame retardancy and anti-aging properties of polymer materials to meet market demand.

[0003] At present, the existing technology is to directly add flame retardants and commercial small molecule antioxidants to polymer materials to achieve flame retardant and anti-aging functions. Antioxidants are mostly small molecule compounds. During processing and use, they are not only easy to volatilize and migrate and lose their antioxidant properties, but also when the amount added is relatively high, a "frost spraying" phenomenon will occur, polluting the environment in which the polymer material is used. Hu et al. (Journal of Hazardous Materials 352 (2018) 92-100) showed that during the long-term service of flame retardant materials, flame retardant elements and flame retardants will migrate to the surface of the material, resulting in the precipitation of flame retardants, thereby reducing the flame retardant properties of the polymer material. Therefore, directly adding flame retardants and antioxidants to polymer materials will cause the antioxidants and flame retardants to migrate and precipitate during long-term use, resulting in poor anti-aging and flame retardant properties of the polymer material.

[0004] More and more studies have shown that microencapsulation technology can improve the compatibility of flame retardants in polymers and the durability of flame retardant materials, and can significantly improve the flame retardant properties of microencapsulated flame retardant flame retardant materials. Free radical polymerization is a commonly used method for preparing microencapsulated polymer shells. It uses olefin monomers containing unsaturated double bonds as raw materials, opens the double bonds in the monomer molecules, and repeatedly performs addition reactions between molecules to connect many monomers to form macromolecules. The present invention prepares the polymer shell by copolymerization of double-bond free radicals. The condensation molecular weight grows slowly at the beginning, and the subsequent growth rate accelerates. The free radical copolymerization molecular weight is independent of time, and the molecular weight grows rapidly after initiation. A layer of polymer is wrapped on the surface of the flame retardant through free radical polymerization, so that the flame retardant has hydrophobic, lipophilic, and polymer-philic surface and interface characteristics, which will make the flame retardant have better compatibility in the matrix and reduce the damage to the mechanical properties of the material due to the addition of flame retardants.

[0005] Phosphorus-containing compounds are a class of excellent flame retardants, and substances containing low-valent phosphorus are used as hydroperoxide decomposers. They can reduce the hydroperoxides released by polymer materials to alcohols, while they themselves are oxidized to phosphates. For example, phosphites are often used as halogen-free flame retardants and antioxidants. 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO, phosphorus is +1 valence) and diphenylphosphinoyl chloride (DC, phosphorus is +1 valence) are new flame retardant intermediates. Flame retardants containing low-valent phosphorus mainly improve flame retardancy through gas phase flame retardant mechanism. In addition, hindered phenols can not only effectively remove free radicals in the body of the substance and play an antioxidant role, but also have a certain gas phase flame retardant effect. However, there are no reports on the research of +1 valence phosphorus-containing flame retardants and hindered phenols encapsulated on the surface of flame retardants through double bond polymerization. Therefore, it is of great significance to prepare core-shell flame retardants with thermal oxidative aging resistance by free radical polymerization of compounds containing low-valent phosphorus or hindered phenols and apply them to the flame retardant and antioxidant research of polymer composites. Summary of the invention

[0006] In order to overcome the problem that the flame retardant and antioxidant in the existing flame retardant polymer material migrate and precipitate during long-term use, resulting in the deterioration of the anti-aging performance and flame retardant performance of the polymer material, the present invention provides a core-shell structure flame retardant with anti-thermal oxygen aging function and its application in the preparation of flame retardant materials. The flame retardant of the present invention can not only give the polymer composite material good flame retardant and mechanical properties, but also solve the problem of long-term heat aging resistance of the flame retardant polymer composite material.

[0007] The flame retardant of the present invention has a core-shell structure, and the shell layer is formed by free radical copolymerization of double-bond phosphorus-containing flame retardant monomers or double-bond hindered phenol monomers on the surface of the core flame retardant to form a flame retardant polymer shell layer. The shell layer can not only change the surface and interface characteristics and water resistance of the flame retardant, but also has flame retardant properties, which can play a synergistic flame retardant role with the core flame retardant. In addition, the low-valent phosphorus or hindered phenol in the shell layer can give the core-shell flame retardant an antioxidant function, thereby improving the aging resistance life of the material.

[0008] The invention discloses a core-shell flame retardant with heat-oxidative aging resistance, which is composed of a core and a shell structure, wherein the core is a flame retardant, and the shell structure is a polymer containing hindered phenol and low-valent phosphorus, and the mass ratio of the core layer to the shell structure is 100:5-25.

[0009] The flame retardant is selected from one or more of magnesium hydroxide, aluminum hydroxide, metal double hydroxide, basic magnesium carbonate, basic lanthanum carbonate, basic cerium carbonate, melamine phosphate, melamine polyphosphate, melamine cyanurate, pentaerythritol, ammonium polyphosphate, piperazine pyrophosphate, aluminum hypophosphite, aluminum phosphite, carbon former, expandable graphite, zinc borate, graphene, transition metal disulfide, carbon nanotubes, halloysite, sepiolite, and kaolin, and mixed in any proportion.

[0010] The preparation method of the core-shell structure flame retardant with anti-thermal oxygen aging function of the present invention comprises the following steps: Add flame retardant (FR) to the solvent, stir and disperse evenly under nitrogen atmosphere, add antioxidant functional double bond monomer and free radical initiator, raise the temperature to 60-80°C and react for 4-12h; after the reaction, cool to room temperature, filter and wash, and dry the obtained product in an oven at 60-80°C to constant weight to obtain a solid product.

[0011] The free radical initiator is selected from one or more of cyclohexanone peroxide, dibenzoyl peroxide, tert-butyl hydroperoxide, azobisisobutyronitrile, and azobisisoheptanenitrile. The amount of the free radical initiator added is 0.5%-5% of the antioxidant functional double bond monomer.

[0012] The solvent is selected from one or more of tetrahydrofuran, dimethyl sulfoxide, cyclohexane, cyclohexanone, chloroform, toluene, xylene, benzene, dioxane, ethyl acetate, acetone, butanone and the like.

[0013] The antioxidant functional double-bond monomer is selected from one or more of DHA, DCHA, HHA and HDPP, and the structure is shown below: .

[0014] Different monomers can be combined and copolymerized to exert flame retardant effects of different structures. The synergistic effect makes the flame retardant more efficient than the shell prepared by polymerization of a single monomer.

[0015] The synthetic route of the antioxidant functional double bond monomer includes: Route 1: Add DOPO to the solvent, stir, and heat to 40-60°C. After DOPO is completely dissolved, add hydroxyethyl acrylate and triethylamine, and stir at this temperature for 30 minutes. Then add carbon tetrachloride dropwise and react for 4-8 hours. After the reaction is completed, cool to room temperature, wash with hydrochloric acid, saturated brine and sodium bicarbonate solution, remove water with anhydrous magnesium sulfate, filter and evaporate to recover the solvent, and obtain the product DHA (DOPO grafted hydroxyethyl acrylate).

[0016] Route 2: Add hydroxyethyl acrylate and triethylamine to a solvent, stir, and heat to 40-60°C. After uniform dispersion, add diphenylphosphinyl chloride dropwise to the above solution and react for 4-8 hours. After the reaction is completed, cool to room temperature, wash with hydrochloric acid, saturated brine and sodium bicarbonate solution, remove water with anhydrous magnesium sulfate, filter and rotary evaporate to recover the solvent, and obtain the product DCHA (diphenylphosphinyl chloride grafted hydroxyethyl acrylate).

[0017] Route 3: Add 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid to the reaction system of thionyl chloride and solvent, heat to 40-60°C in a nitrogen atmosphere and react for 4-8 hours; after the reaction is completed, cool to room temperature, and recover the solvent by rotary evaporation to obtain a viscous liquid product (3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride). Add hydroxyethyl acrylate and triethylamine to the solvent, stir, heat to 40-60°C, and after uniform dispersion, add 3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride dropwise to the above solution and react for 4-8 hours; after the reaction is completed, cool to room temperature, wash with hydrochloric acid, saturated brine and sodium bicarbonate solution, remove water with anhydrous magnesium sulfate, filter and rotary evaporation to recover the solvent, and obtain the product HHA (3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride grafted with hydroxyethyl acrylate).

[0018] Route 4: Add hydroxyethyl acrylate and triethylamine to a solvent, stir, and heat to 40-60°C. After they are evenly dispersed, add diphenyl chlorophosphate dropwise to the above solution and react for 4-8 hours. After the reaction is completed, cool to room temperature, wash with hydrochloric acid, saturated brine and sodium bicarbonate solution, remove water with anhydrous magnesium sulfate, filter and rotary evaporate to recover the solvent, and obtain the product HDPP (diphenyl phosphate grafted hydroxyethyl methacrylate).

[0019] The invention discloses application of a core-shell structure flame retardant with heat-oxidation aging resistance function in preparing flame retardant materials.

[0020] Specifically, the core-shell structure flame retardant is added to a polymer matrix, mixed in an internal mixer or an extruder at 120-250° C. until uniform, and then a crosslinking agent and a lubricant are added. After mixing uniformly, the mixture is vulcanized in a flat vulcanizer for different times to prepare a flame-retardant polymer composite material.

[0021] The components include, by weight: 40-90 parts of polymer, 10-60 parts of core-shell structure flame retardant, 0-1.5 parts of crosslinking agent and 0-1 part of lubricant.

[0022] The polymer matrix is ​​selected from one or more of polyethylene, EPDM, polypropylene, ethylene-vinyl acetate copolymer, ethylene-octene copolymer, styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, natural rubber, chloroprene rubber, silicone rubber, polyurethane, polyurea, polyamide, polyester, polycarbonate, polylactic acid, polystyrene, thermoplastic elastomer, epoxy resin, unsaturated polyester and the like.

[0023] The crosslinking agent is selected from one of dicumyl peroxide, triallyl cyanurate, triallyl isocyanurate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, or a mixture of several of them in any proportion.

[0024] The lubricant is selected from one of silicone powder, zinc stearate, paraffin wax, and PE wax, or a mixture of several of them in any proportion.

[0025] The core-shell flame retardant with heat-oxidative aging resistance of the present invention has excellent flame retardant and antioxidant functions of long-term migration resistance and precipitation resistance when used in polymer materials, thereby meeting the requirements of long-term flame retardant and heat-oxidative aging resistance of polymer materials.

[0026] Compared with the prior art, the present invention has the following beneficial effects: 1. The core-shell microencapsulated flame retardant with heat-oxidative aging resistance for polymers proposed by the present invention abandons the traditional small molecule antioxidants, and adopts the interface regulation technology to polymerize the hindered phenols or low-valent phosphorus compounds containing double bonds on the surface of the core-shell flame retardant through free radicals to form a polymer shell layer with heat-oxidative aging resistance, thereby obtaining a high molecular weight antioxidant, so that the antioxidant has the effects of migration resistance and precipitation resistance, and exerts the heat-oxidative aging resistance effect for a long time during the service life of the polymer material. It is used to prepare antioxidant polymer composite materials, which have excellent long-term heat-oxidative aging resistance.

[0027] 2. The present invention proposes a core-shell flame retardant with heat-oxidative aging resistance for polymers. Low-valent phosphorus or hindered phenol compounds are introduced into the flame retardant shell. The shell contains a benzene ring structure and phosphorus element with carbon-forming function. It can not only play a core-shell synergistic flame retardant role with the core flame retardant, but also the +5 and +1 / 3 phosphorus composite shells and the hindered phenol and low-valent phosphorus composite shells themselves can play a gas-phase and condensed-phase synergistic flame retardant role. Applying the core-shell flame retardant to polymers can improve the flame retardant properties and flame retardant grade of flame retardant materials; during the combustion process, low-valent phosphorus flame retardants and hindered phenols will capture free radicals and interrupt the combustion chain reaction, thereby playing a gas-phase flame retardant role, and high-valent phosphorus will play a condensed-phase flame retardant role, further improving the flame retardant properties of flame-retardant polymer materials.

[0028] 3. The present invention proposes a core-shell flame retardant with anti-thermal oxidative aging function for polymers. The microencapsulated shell layer is an organic macromolecular polymer, which can improve the interfacial compatibility between the flame retardant and the polymer, thereby improving the compatibility of the flame retardant in the polymer, thereby improving the mechanical properties of the polymer material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The schematic diagram of the synthesis route of the present invention is shown in FIG.

[0030] Figure 2 Corresponding hydrogen spectrum (a) and phosphorus spectrum (b) of DHA.

[0031] Figure 3 The corresponding hydrogen spectrum (a) and phosphorus spectrum (b) of DCHA.

[0032] Figure 4 Corresponding to the hydrogen spectrum of HHA.

[0033] Figure 5 The corresponding hydrogen spectrum (a) and phosphorus spectrum (b) of HDPP.

[0034] Figure 6 Corresponding contact angle test pictures of APP and DHA@APP.

[0035] Figure 7 Corresponding contact angle test pictures of MH and HHA@MH.

[0036] Figure 8 Corresponding to the changes in oxidation induction time of each sample extracted in acetone for 5 days.

[0037] Fig. 9 Corresponding contact angle test pictures of PAPP and DCHA@PAPP.

[0038] Fig.10 Corresponding contact angle test pictures of MPP and DCHA@MPP. DETAILED DESCRIPTION

[0039] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. Based on the examples in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. Embodiment 1:

[0040] 1. Add 2.16 g DOPO to 300 mL chloroform and stir, and heat to 40°C. After DOPO is completely dissolved, add 1.16 g hydroxyethyl acrylate and 2.02 g triethylamine, and stir at this temperature for 1 h. Then add 2.31 g carbon tetrachloride dropwise and react for 6 h. After the reaction is completed, cool to room temperature, wash with 1 mol / L hydrochloric acid, saturated salt water and 1 mol / L sodium bicarbonate solution, and remove water with anhydrous magnesium sulfate. Recover the solvent by rotary evaporation to obtain the product DHA (DOPO grafted hydroxyethyl acrylate).

[0041] 2. Add 1.16 g of hydroxyethyl acrylate and 2.02 g of triethylamine to 300 mL of tetrahydrofuran, stir, and heat to 50°C. After the mixture is evenly dispersed, add 3.56 g of diphenylphosphinyl chloride dropwise to the solution and react for 5 hours. After the reaction is completed, cool to room temperature, wash with 1 mol / L hydrochloric acid, saturated saline, and 1 mol / L sodium bicarbonate solution, and remove water with anhydrous magnesium sulfate. Recover the solvent by rotary evaporation to obtain the product DCHA (diphenylphosphinyl chloride grafted hydroxyethyl acrylate).

[0042] 3. Add 5.56g (0.02 mol) of 3,5-di-tert-butyl-4-hydroxybenzene propionic acid to a 250 mL three-necked flask and add 100 mL of chloroform to dissolve it. Slowly drop 4 mL of thionyl chloride under nitrogen protection and react at 50°C for 5 h. After the reaction is completed, remove the solvent and unreacted thionyl chloride by vacuum distillation to obtain 3,5-di-tert-butyl-4-hydroxybenzene propionyl chloride. Add 2.3 g of hydroxyethyl acrylate and 4 g of triethylamine to chloroform, stir, and heat to 60°C. After it is evenly dispersed, add 5.56g of 3,5-di-tert-butyl-4-hydroxybenzene propionyl chloride dropwise to the above solution and react for 7 h. After the reaction is completed, cool to room temperature, wash with 1 mol / L hydrochloric acid, saturated brine and 1 mol / L sodium bicarbonate solution, and remove water with anhydrous magnesium sulfate. The solvent was recovered by rotary evaporation to obtain the product HHA (3,5-di-tert-butyl-4-hydroxyphenylpropionyl chloride grafted with hydroxyethyl acrylate).

[0043] 4. Add 1.16g of hydroxyethyl acrylate and 2.02g of triethylamine to 300mL of tetrahydrofuran, stir, and heat to 50°C. After being evenly dispersed, add 2.69g of diphenylphosphinyl chloride dropwise to the above solution and react for 7h. After the reaction is completed, cool to room temperature, wash with 1mol / L hydrochloric acid, saturated salt water and 1mol / L sodium bicarbonate solution, and remove water with anhydrous magnesium sulfate. Recover the solvent by rotary evaporation to obtain the product HDPP (diphenyl phosphate grafted hydroxyethyl acrylate). Embodiment 2:

[0044] 1. Add 100 g of ammonium polyphosphate (APP) into a 500 mL three-necked flask and stir with nitrogen. After uniform dispersion, add 10 g of DHA and 0.2 g of cyclohexanone peroxide. After dissolution, heat to 80 °C and react for 6 h. After the reaction is completed, cool to room temperature, filter, wash and dry. The obtained product is dried in an oven at 60 °C to constant weight to obtain a solid product (DHA@APP).

[0045] 2. Add 12 parts of aging-resistant core-shell flame retardant (DHA@APP) and 4 parts of triazine macromolecular carbonizing agent (CFA) to 84 parts of ethylene propylene diene monomer rubber (EPDM) by mass ratio, then add 0.6 parts of triallyl cyanurate (TAIC) and 0.6 parts of diisopropylbenzene peroxide (DCP), then mix in an internal mixer or extruder at 90-100°C until uniform extrusion granulation, and vulcanize at 160°C in a flat vulcanizer for 15 minutes to make a sheet.

[0046] To further verify the performance of the aging-resistant core-shell flame retardant DHA@APP, we designed the following materials as shown in Tables 1, 2, 3, 4 and Figure 5 The comparative formula shown is used to compare the comprehensive physical property test results of the two. Table 1 is the formula table of durable antioxidant flame retardant polymer composite materials and the vertical combustion and oxygen index test results; Table 2 is the data table of the mechanical property changes of durable antioxidant flame retardant polymer composite materials before and after being placed in a 125°C heat aging oven for 100 hours; Table 3 is the mechanical property test table of each sample of durable antioxidant flame retardant polymer composite materials resistant to refrigerant R134a / R1234yf and refrigeration oil POE / PAG (10:1), pre-aging at 90°C×96h and then aging at 150°C×168h; Table 4 is the compression permanent deformation test table of durable antioxidant flame retardant polymer composite materials at 130°C×96h×40%; Figure 5 These are the contact angle test pictures of APP and DHA@APP.

[0047]

[0048]

[0049]

[0050] Embodiment 3:

[0051] 1. Add 100 g of magnesium hydroxide (MH) to a 500 mL three-necked flask and stir with nitrogen. After uniform dispersion, add 2 g of HHA, 8 g of DHA and 0.8 g of azobisisobutyronitrile. After dissolving, heat to 70 °C for 8 h. After the reaction is completed, cool to room temperature, filter, wash and dry. The obtained product is dried in an oven at 60 °C to constant weight to obtain a solid product (DH@MH).

[0052] 2. Add 60 parts of aging-resistant core-shell flame retardant (DH@MH) to 40 parts of ethylene propylene diene monomer (EPDM) by mass ratio, then add 0.5 parts of trimethylolpropane trimethacrylate (TPT) and 0.4 parts of diisopropylbenzene peroxide (DCP), add 1 part of silicone powder, then mix in an internal mixer or extruder at 100-120°C until uniform, extrude and granulate, and vulcanize in a flat vulcanizer at 165°C for 15 minutes to make a sheet.

[0053] To further verify the performance of the aging-resistant core-shell flame retardant DH@MH, we designed the following materials as shown in Tables 5, 6 and Figure 6 , 7 The comparative formula shown is used to compare the comprehensive physical property test results of the two. Table 7 is the formula table of the durable antioxidant flame retardant polymer composite material and the vertical combustion and oxygen index test results; Table 8 is the data table of the mechanical property changes of the durable antioxidant flame retardant polymer composite material before and after being placed in a 180 ℃ heat aging oven for 14 days; Table 9 is the data table of the mechanical property changes of the durable antioxidant flame retardant polymer composite material before and after being placed in a 180 ℃ heat aging oven for 14 days; Figure 6 These are the contact angle test pictures of MH and DH@MH; Figure 7 This is a data chart showing the changes in oxidation induction time of each sample after extraction in acetone for 5 days.

[0054]

[0055] Embodiment 4:

[0056] 1. Add 100 g of piperazine pyrophosphate (PAPP) to a 500 mL three-necked flask and stir with nitrogen. After uniform dispersion, add 15 g of DCHA and 1 g of dibenzoyl peroxide. After dissolving, heat to 75°C and react for 7 hours. After the reaction is completed, cool to room temperature, filter, wash and dry. The obtained product is dried in an oven at 60°C to constant weight to obtain a solid product (DCHA@APP).

[0057] 2. Add 28 parts of anti-aging core-shell flame retardant (DCHA@PAPP) to 72 parts of polyethylene (PE) by mass ratio, then add 0.8 parts of triallyl isocyanurate (TAIC) and 0.4 parts of diisopropylbenzene peroxide (DCP), then mix them in an internal mixer or extruder at 110-115°C until uniform, extrude and granulate, and vulcanize them at 165°C in a flat vulcanizer for 12 minutes to make a sheet.

[0058] To further verify the performance of the aging-resistant core-shell flame retardant DCHA@PAPP, we replaced it with uncoated PAPP and PAPP and DCHA blends in equal amounts and applied it to the flame retardant system of PE. We designed the comparative formulas shown in Tables 7 and 8 to compare the comprehensive physical property test results of the two. Table 7 is the formula table of durable antioxidant flame retardant polymer composite materials and the vertical combustion and oxygen index test results; Table 8 is the data table of mechanical property changes of durable antioxidant flame retardant polymer composite materials before and after being placed in a 150°C heat aging oven for 125 days; Figure 8 These are the contact angle test pictures of PAPP and DCHA@PAPP.

[0059]

[0060] Embodiment 5:

[0061] 1. Add 100 g of melamine polyphosphate (MPP) to a 500 mL three-necked flask and stir with nitrogen. After uniform dispersion, add 20 g of DCHA and 1 g of azobisisoheptanenitrile. After dissolving, heat to 75°C and react for 7 hours. After the reaction is completed, cool to room temperature, filter, wash and dry. The obtained product is dried in an oven at 60°C to constant weight to obtain a solid product (DCHA@MPP).

[0062] 2. Add 16 parts of aging-resistant core-shell structure flame retardant (DCHA@PAPP) to 84 parts of thermoplastic polyurethane (TPU) by mass ratio, then mix them in an internal mixer or extruder at 180°C until uniform, extrude granules at 190°C after mixing evenly, and press them into sheets in a flat vulcanizer.

[0063] To further verify the performance of the aging-resistant core-shell flame retardant DCHA@MPP, we replaced it with uncoated MPP and MPP and DCHA blends in equal amounts and applied it to the flame retardant system of TPU. We designed the comparative formulas shown in Tables 9 and 10 to compare the comprehensive physical property test results of the two. Table 9 is the formula table of durable antioxidant flame retardant polymer composite materials and the vertical combustion and oxygen index test results; Table 10 is the data table of mechanical property changes of durable antioxidant flame retardant polymer composite materials before and after being placed in a 150°C thermal aging oven for 125 days; Fig. 9These are the contact angle test pictures of MPP and DCHA@MPP.

[0064]

[0065] Embodiment 6:

[0066] 1. Add 100 g aluminum hypophosphite (AHP) to a 500 mL three-necked flask and stir with nitrogen. After uniform dispersion, add 10 g DCHA, 10 g HDPP and 1 g azobisisoheptanitrile. After they are dissolved, heat to 80 °C and react for 6 h. After the reaction is completed, cool to room temperature, filter, wash and dry. The obtained product is dried in an oven at 60 °C to constant weight to obtain a solid product (DP@AHP).

[0067] 2. Add 52 parts of aging-resistant core-shell flame retardant (DP@AHP) to 48 parts of thermoplastic elastomer (TPE) by mass ratio, then mix them in an internal mixer or extruder at 185°C until uniform. After mixing evenly, extrude and granulate them at 195°C, and press them into sheets in a flat vulcanizer.

[0068] To further verify the performance of the aging-resistant core-shell flame retardant DP@MPP, we replaced it with uncoated AHP and AHP, DCHA and HDPP blends in equal amounts and applied it to the flame retardant system of TPE. We designed the comparative formulas shown in Tables 11 and 12 to compare the comprehensive physical property test results of the two. Table 11 is the formula table of the durable antioxidant flame retardant polymer composite material and the vertical combustion and oxygen index test results; Table 12 is the data table of the mechanical property changes of the durable antioxidant flame retardant polymer composite material before and after being placed in a 150°C heat aging oven for 125 days.

[0069]

[0070]

[0071] Based on the above experimental results, the following conclusions are drawn: (1) The hydrophobicity of the synthesized core-shell flame retardant with anti-thermal oxidative aging function is improved. On the other hand, the compatibility and dispersibility of the anti-aging core-shell flame retardant in organic polymer materials are also improved.

[0072] (2) The composite materials with core-shell flame retardants having anti-thermal oxidative aging function have better physical and mechanical properties and flame retardant properties than the flame retardant composite materials with small molecule antioxidants.

[0073] (3) After long-term heat aging test, the composite material with core-shell flame retardant having anti-thermal oxidative aging function showed a better decline in mechanical properties than other composite materials.

Claims

1. A core-shell flame retardant with anti-thermal oxygen aging function, characterized in that: The core-shell flame retardant with heat-oxidative aging resistance is composed of a core and a shell structure, wherein the core is a flame retardant, the shell structure is a polymer containing hindered phenol and low-valent phosphorus, and the mass ratio of the core layer to the shell structure is 100:5-25.

2. The core-shell flame retardant with heat-oxidative aging resistance according to claim 1, characterized in that: The flame retardant is selected from one or more of magnesium hydroxide, aluminum hydroxide, metal double hydroxide, basic magnesium carbonate, basic lanthanum carbonate, basic cerium carbonate, melamine phosphate, melamine polyphosphate, melamine cyanurate, pentaerythritol, ammonium polyphosphate, piperazine pyrophosphate, aluminum hypophosphite, aluminum phosphite, carbon former, expandable graphite, zinc borate, graphene, transition metal disulfide, carbon nanotubes, halloysite, sepiolite, and kaolin, and mixed in any proportion.

3. The method for preparing the core-shell flame retardant with heat-oxidative aging resistance according to claim 1 or 2, characterized in that The steps include: Add the flame retardant to the solvent, stir and disperse evenly under a nitrogen atmosphere, add the antioxidant functional double bond monomer and the free radical initiator, raise the temperature to 60-80°C and react for 4-12 hours; after the reaction, cool to room temperature, filter and wash, and dry to constant weight to obtain a solid product; The antioxidant functional double-bond monomer is selected from one or more of DHA, DCHA, HHA, and HDPP, and the structure is shown below: 。 4. The preparation method according to claim 3, characterized in that: The free radical initiator is selected from one or more of cyclohexanone peroxide, dibenzoyl peroxide, tert-butyl hydroperoxide, azobisisobutyronitrile and azobisisoheptanenitrile.

5. The preparation method according to claim 3, characterized in that: The solvent is selected from one or more of tetrahydrofuran, dimethyl sulfoxide, cyclohexane, cyclohexanone, chloroform, toluene, xylene, benzene, dioxane, ethyl acetate, acetone, butanone and the like.

6. Use of the core-shell structure flame retardant with heat-oxidative aging resistance function as claimed in claim 1 or 2 in the preparation of flame retardant materials.

7. The use according to claim 6, characterized in that: The core-shell structure flame retardant is added to a polymer matrix, mixed in an internal mixer or an extruder at 120-250° C. until uniform, and then a crosslinking agent and a lubricant are added, mixed uniformly, and then vulcanized to prepare a flame-retardant polymer composite material.

8. The use according to claim 7, characterized in that: The components include, by weight: 40-90 parts of polymer, 10-60 parts of core-shell structure flame retardant, 0-1.5 parts of crosslinking agent and 0-1 part of lubricant.

9. The use according to claim 7, characterized in that: The polymer matrix is ​​selected from one or more of polyethylene, EPDM, polypropylene, ethylene-vinyl acetate copolymer, ethylene-octene copolymer, styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, natural rubber, chloroprene rubber, silicone rubber, polyurethane, polyurea, polyamide, polyester, polycarbonate, polylactic acid, polystyrene, thermoplastic elastomer, epoxy resin, unsaturated polyester and the like.

10. The use according to claim 7, characterized in that: The crosslinking agent is selected from one of dicumyl peroxide, triallyl cyanurate, triallyl isocyanurate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, or a mixture of several of them in any proportion.

Citation Information

Patent Citations

  • Organosilicon-phosphorus-containing acrylate core-shell toughening flame retardant and preparation method thereof

    CN114292368A

  • Durable antioxidant flame-retardant polymer composite material and preparation method thereof

    CN114874534A

  • Oxidation-resistant carbon nanotube modified polyethylene composite material and preparation method thereof

    CN116462900A

  • Halogen-free flame-retardant antioxidant cross-linked polyolefin composite material and preparation method thereof

    CN117384445A

Cited By

  • Anti-tearing steel wire rope core conveying belt and preparation process thereof

    CN120535843A

  • Preparation method of additive type nitrogen-phosphorus-lanthanum synergistic flame-retardant polyurethane elastomer

    CN120718243A

  • Wave-absorbing core-shell structure super-surface composite material for unmanned aerial vehicle and preparation method thereof

    CN120757395A

  • Coated spherical silicon dioxide flame retardant and preparation method thereof

    CN120923868A

  • Low-smoke and low-toxicity steel wire rope core flame-retardant conveying belt for coal mine and preparation method thereof

    CN121757519A